Implementasi Teknik Scaffolding Untuk Mengembangkan Kecerdasan Kognitif Anak Usia Dini - Amanullah, Akhmad Syah Roni; Wulaningsih, Endang Sri; Sari, Indrayani Nurdiana (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study departs from the problem where early childhood experiences delays in cognitive development. The delay in cognitive development is due to the learning model provided by parents or teachers which is still limited to providing advice and "warnings", even though early childhood in the pre-operational period needs an example of real actions so that children are easier to understand and take action. This study aims to develop AUD cognitive intelligence through scaffolding techniques so that children's cognitive development can develop well and quickly. This study uses descriptive qualitative research, where in this study the researcher provides clear and operational explanations and descriptions regarding the use of scaffolding techniques as an appropriate and fast way to develop children's cognitive intelligence. In this study, it was found that the use of scaffolding techniques can help parents and teachers in developing and training cognitive intelligence in children. Children's cognitive intelligence can be seen from children starting to be able to put on and take off shoes properly and correctly.